АНАЛІЗ РЕЗУЛЬТАТІВ ЕКСПЕРИМЕНТАЛЬНИХ ДОСЛІДЖЕНЬ НЕОДНОРІДНОСТІ МЕРЕЖІ ПОСТІЙНОГО СТРУМУ - Гребченко, М.В.; Сопель, М.Ф.; Сподинський, О.В. (Інститут електродинаміки НАН України, Київ, 2024)
The modes of breakage of one line of network sections with parallel lines in electrical distribution networks of power supply to consumers of direct current electric transport have been studied. An analysis of the experimental data was carried out, the results of which indicate the presence of a dependence of the value of the variable component in the rectified current on the distance to the damaged area. Mathematical modeling of the breakage mode of one of the line sections in the network with a serial connection of three sections, each of which has parallel lines, has been carried out. The obtained results of mathematical modeling of the modes of operation of a direct current network with heterogeneity of different sections also indicate the possibility of using the sixth harmonic of the current to determine the occurrence of heterogeneity and the section with this heterogeneity. To reduce the influence of load changes when determining an inhomogeneous section, it is proposed to control the input impedance of the network at a frequency of 300 Hz. It has been established that in these regimes the resistance angle changes the most. A method for determining the occurrence of local damage to a direct current line and the distance to this damage location is proposed, which is based on monitoring the value of the line current and the input resistance of the line at a frequency of 300 Hz. References 7, Figures 4, Tables 2.